The Importance of Family Participation in Homework: Understanding the Relationship Between Student Homework Behaviors and Academic Achievement by School Level - Avcı, Süleyman; Özgenel, Mustafa; Avcu, Akif; Özgenel, Mustafa (Springer, 2025)
The purpose of this study was to examine in detail the relationship between per-ceived parental involvement in homework (content-oriented and autonomy-oriented forms of involvement) and students’ homework behavior (homework time, home-work time management, and amount of homework completed). The study also looked at how the relationships between these variables change between middle school and high school. The study was conducted on 528 middle and high school students in grades 5–12. The relationships between the variables used in the study were structured using a theoretical model and tested using the structural equation model method. The results of the study show that parental involvement in home-work has a positive relationship with students’ homework behaviour. In particu-lar, time management skills have the strongest relationship with parental involve-ment among the three homework behaviors. However, while there was no direct relationship between parental involvement and overall academic achievement, parental involvement in homework showed a positive relationship with academic achievement through homework completion and time management. At the second-ary school level, there is a positive relationship between students’ homework time, homework completion and time management skills and academic achievement. Stu-dents’ homework completion stood out as the variable with the strongest relation-ship with academic achievement. These findings suggest that parental involvement in the homework process, especially at the secondary school level, can help students to manage their homework more effectively and be more successful academically.
Keywords: Academic achievement; Homework behavior; Parental homework involvement